Effect of selected chemicals on inducing relaxation in the dog conch Laevistrombus canarium (Linnaeus, 1758) - Venkatesan, V.; Kalidas, C. (Indian Journal of Fisheries, 2014)
Adult dog conchs Laevistrombus canarium (60.6Â±1.23 mm shell length) were subjected to selected potential relaxant chemicals viz., magnesium chloride (MgCl2), magnesium sulphate (MgSO4), EDTA (ethylenediaminetetraacetic acid disodium), 2-phenoxyethanol (PE), menthol (ME) and the time taken to induce relaxation and recovery were studied. All the treatments were observed continuously for 30 min post-exposure. Among the selected relaxants, MgCl2 (30 g l-1) successfully induced adequate relaxation in 24.5 min. Relaxed conch presented an extended mantle and exhibited slow reaction to physical manipulation. Conchs exposed to all other treatments, retracted into their shells and did not show any sign of relaxation during the exposure period.